Application of Indigenous Traditional Songs ‘Sewang’ in Preschool Teaching and Learning - Narasid, Siti Nor Khalis Harun; Rahman, Mohd Nazri Abdul (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2025)
This study aims to examine the application of traditional Orang Asli songs in teaching and learning in preschool education. Traditional songs of the Orang Asli community have significant educational potential in fostering language development, cultural appreciation, and socio-emotional growth among preschool children. Using a qualitative approach, this research uses semi-structured interviews with preschool teachers. This study also uses document analysis of selected traditional songs to support the interview findings. Findings obtained from interviews with preschool teachers show that the application of traditional Orang Asli songs in the classroom has the potential to improve phonological awareness, vocabulary acquisition, and motor skills through group singing and movement activities. Document analysis of the repetitive lyrics and simple melodies of these traditional songs, themed around nature, community, and moral values, contributes to the preservation of the cultural heritage of the Orang Asli community. The implications of this study show that the application of traditional songs in teaching can strengthen children's language, as well as ensure the sustainability of indigenous culture in early education. This study highlights the use and application of traditional Orang Asli songs in enhancing language development, cultural appreciation, and socio-emotional growth of preschool children, which can then contribute to the preservation of the cultural heritage of the Orang Asli community.